Consumer Buying Interest: Survey of Shopee Consumers in Yogyakarta - Astri Wulandari; Dessy Putri Wahyuni; M. Nastain (JCommsci - Journal Of Media and Communication Science, 2021)
The digital era has led consumer behavior to shop online. It is undeniable that online shopping is indeed more in demand by some consumers because of various supporting factors. Shopee is an online shop application with many features so that consumers can easily shop, explore and even easily create an online store and sell products. This study uses quantitative research methods to see the effect of buying interest in Shopee online shopping in Yogyakarta. Sources of data were obtained from primary and secondary data with cluster sampling technique to 500 respondents. The results showed that each indicator of buying interest showed positive and significant results. The Transactional Interest indicator is included in the value category with a percentage of 34%, and then for Reference Interest, it has a percentage order of 69% with a very high category. Then for Preferential Interest, the order of category is very high at 70%, and Explanative Interest with a high percentage category at 58%.